Sosialisasi Undang - Undang Nomor 7 Tahun 2021 Tentang Harmonisasi Peraturan Perpajakan Pada UMKM di Wilayah Sambiroto Semarang - Apip Apip; Dul Muid; Clara Ekaristi; Sukma Firdaus (Yayasan Sumber Daya Manusia Cerdas, 2024)
This community service activity aims to socialize the law on harmonization of tax regulations to Micro, Small and Medium Enterprises (MSMEs) in Sambiroto Village, Semarang City. Through an empowerment and mentoring approach, this program aims to increase tax understanding and awareness for MSMEs, especially regarding new tax regulations. Activity methods include site surveys, preparation for visits, discussions and outreach regarding tax provisions for MSMEs. The survey results show that further socialization is still needed regarding Law number 7 of 2021 concerning Harmonization of Tax Regulations, especially regarding taxable and non-taxable income for MSMEs. In its implementation, this program received a positive response from the community with good participation from MSME owners. They feel helped by new knowledge regarding tax regulations, but also hope for further assistance activities in preparing financial reports. Thus, it can be concluded that this program has succeeded in increasing public understanding, especially MSMEs, regarding tax regulations. The positive response from the community shows that needs have been met and hopes for further support in terms of tax assistance and socialization.